Distillating greenhouses - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Using brackish or even sea water to irrigate plants is now possible thanks to a solar distillation greenhouse. The water to be distilled is circulated in the upper levels of the greenhouse and condenses on the inner surfaces of the roof which it...